Persepsi Mahasiswa UM-Sorong Terhadap Kuliah Online Saat Wabah Covid-19 di Kota Sorong - Nanik Purwanti; Mei Menselina Safkaur (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study tries to determine students' perceptions of online lectures, and to find out the supporting and inhibiting factors in online lectures. The data collection technique used in this study was by means of field research consisting of observations, interviews, and documentation as well as the distribution of questionnaires via google drive. patterns of life and interactions due to the application of online learning. Online lectures using various advanced features cannot replace the role of lecturers through face-to-face lectures, because they provide more motivation and enthusiasm for students to learn than attending lectures through distance lectures (online). Considering that the current pattern of interaction and learning among students is different, and they are also in the adjustment stage. This can be concluded as a complex problem, about the social reality that has occurred and is predicted among students.